PARADOKS TEKNOLOGI: ANTARA KEMUDAHAN DAN KEMANDEGAN INTELEKTUAL MAHASISWA DALAM PEMBELAJARAN PAI DI KAMPUS POLINEMA PSDKU KEDIRI - Muhammad Ibnu Huda; Suko Susilo; Muhammad Yunus (PT. Saha Kreasi Indonesia, 2025)
The development of digital technology, particularly Artificial Intelligence (AI), has brought significant changes to the field of education, including Islamic Religious Education (PAI). This study aims to describe the impact of AI usage on students’ intellectual abilities and independent thinking. The research employed a descriptive qualitative method, with participants consisting of 25 first-semester students at a state polytechnic in Kediri City. Data were collected through participatory observation, unstructured interviews, and documentation of learning outcomes. The findings indicate that the use of AI provides students with easier access to information and facilitates task completion; however, it also leads to intellectual stagnation. Students tend to rely on AI for instant answers without engaging in critical and reflective thinking processes. This condition results in weakened analytical skills, argumentative abilities, and internalization of religious values. The study concludes that technology possesses a paradoxical nature: on one hand, it simplifies learning processes, but on the other hand, it may hinder intellectual development if not used wisely. Therefore, PAI lecturers must act as facilitators who guide students to utilize AI as a tool to support thinking, rather than a substitute for thinking.